2010
DOI: 10.1007/s00221-010-2240-4
|View full text |Cite
|
Sign up to set email alerts
|

An extended multisensory temporal binding window in autism spectrum disorders

Abstract: Autism spectrum disorders (ASD) form a continuum of neurodevelopmental disorders, characterized by deficits in communication and reciprocal social interaction, as well as by repetitive behaviors and restricted interests. Sensory disturbances are also frequently reported in clinical and autobiographical accounts. However, surprisingly few empirical studies have characterized the fundamental features of sensory and multisensory processing in ASD. The current study is structured to test for potential differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
323
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 355 publications
(352 citation statements)
references
References 41 publications
25
323
3
1
Order By: Relevance
“…Various researchers have determined that there does exist an extended temporal binding window in ASD, meaning that individuals with ASD continue to integrate sensory information over a larger gap in time than do TD individuals (Foss-Feig et al 2010;Kwakye et al 2011;Woynaroski et al 2013). The current results indicating that the ASD group had significantly lower accuracy than the TD group on the 2F1B (i.e., fusion illusion) and 2F0B trials may be explained by the presence of an expanded temporal binding window.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Various researchers have determined that there does exist an extended temporal binding window in ASD, meaning that individuals with ASD continue to integrate sensory information over a larger gap in time than do TD individuals (Foss-Feig et al 2010;Kwakye et al 2011;Woynaroski et al 2013). The current results indicating that the ASD group had significantly lower accuracy than the TD group on the 2F1B (i.e., fusion illusion) and 2F0B trials may be explained by the presence of an expanded temporal binding window.…”
Section: Discussionmentioning
confidence: 47%
“…Foss Feig et al (2010) studied children with and without ASD on the flash beep task, but specifically looked at temporal binding windows for the fission illusion. They found that children with ASD had approximately a doubly large temporal binding window as compared to the TD group (i.e., they were integrating 2 beeps over a 600 ms window, whereas the TD group was only integrating over 300 ms window.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations